2011
DOI: 10.1590/s0102-33062011000200021
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de caracteres morfoanatômicos foliares na taxonomia de Campomanesia Ruiz & Pavón (Myrtaceae)

Abstract: ABSTRACT(Application of morpho-anatomical leaf characters in Campomanesia Ruiz & Pavón (Myrtaceae) taxonomy). To evaluate the utility of morpho-anatomical leaf characters in the identifi cation of botanic material of Campomanesia Ruiz & Pavón, especially when sterile, leaf venation pattern and shape of the vascular arch in the petiole of 15 taxa in Bahia state were analysed. Th e camptodromous-brochydodromous secondary venation pattern was uniform among the taxa, as well as the ultimate marginal venation in ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
1
5
0
3
Order By: Relevance
“…However, in this study, it was observed that the arrangement and shape of the areola were different and unique for each taxon. These characters were important to differentiate taxa, corroborating to the work from Oliveira et al (2011), where these characters were used to differentiate Myrtaceae species. The free end veins (FEVs) or free venules are commonly composed by two-three branches.…”
Section: Discussionsupporting
confidence: 81%
“…However, in this study, it was observed that the arrangement and shape of the areola were different and unique for each taxon. These characters were important to differentiate taxa, corroborating to the work from Oliveira et al (2011), where these characters were used to differentiate Myrtaceae species. The free end veins (FEVs) or free venules are commonly composed by two-three branches.…”
Section: Discussionsupporting
confidence: 81%
“…Our results showed that the position of vascular bundles on petioles is useful to the group and distinguish species of Banisteriopsis, corroborating the data of Metcalfe & Chalk (1950) and Araújo et al (2010) for Malpighiaceae. Characters related to vascularization patterns of petioles have been widely used to improve the taxonomy of different families of flowering plants, such as Melastomataceae (Reis et al 2004), Myrtaceae (Oliveira et al 2011), Rubiaceae (Moraes et al 2011), Sapotaceae (Almeida Jr. et al 2013) and Leguminosae (Francino 2006;Coutinho et al 2013). Accessory bundles occurred in 40 of 42 species of Banisteriopsis, varying in the number of bundles, sometimes in specimes from the same species.…”
Section: Leaf Anatomymentioning
confidence: 99%
“…While in S. sordida and S. warmingii it is "V" shaped, in S. pauciflora it is arc shaped. Some of these features have been identified in other groups, where they were proved to be useful for taxonomy, as in Campomanesia -Myrtaceae (Oliveira et al 2011), Rubiaceae (Martínez-Cabrera 2009) and in Melastomataceae (Reis et al 2004) in which the distinctive characters were, among others, the vascular system pattern in the petiole.…”
Section: Discussionmentioning
confidence: 99%